1996
DOI: 10.1093/oxfordjournals.humrep.a019189
|View full text |Cite
|
Sign up to set email alerts
|

Ovary and ovulation: Cell-specific localization of nitric oxide synthases (NOS) in the rat ovary during follicular development, ovulation and luteal formation

Abstract: Nitric oxide (NO) has emerged as one of several important intraovarian regulatory factors. In particular, NO has been implicated in the processes of ovulation and atresia-related apoptosis. The aim of the present study was to investigate the presence and distribution of the NO-generating nitric oxide synthase (NOS) enzymes in the ovary during follicular development, ovulation and luteal formation of the equine chorionic gonadotrophin (ECG)/human chorionic gonadotrophin (HCG)-primed rat. NADPH diaphorase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
76
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 2 publications
10
76
0
Order By: Relevance
“…The increased amount of protein in the nucleus and cytoplasm in partially meiotically competent oocytes may be related to the acquisition of meiotic competence and the requirement of nitric oxide synthesis. Our results confirmed that eNOS is a frequently expressed isoform in mammalian oocytes (Van Voorhis et al, 1994;Jablonka-Shariff and Olson, 1997;Nishikimi et al, 2001;Mitchell et al, 2004) and is also abundant in the somatic compartments of the ovary (Zackrisson et al, 1996;Jablonka-Shariff and Olson, 1997;Jablonka-Shariff et al, 1999;Nakamura et al, 1999;Yamagata et al, 2002;Mitchell et al, 2004). The expression and distribution of eNOS in porcine oocytes do not deviate from this pattern Takesue et al, 2003).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The increased amount of protein in the nucleus and cytoplasm in partially meiotically competent oocytes may be related to the acquisition of meiotic competence and the requirement of nitric oxide synthesis. Our results confirmed that eNOS is a frequently expressed isoform in mammalian oocytes (Van Voorhis et al, 1994;Jablonka-Shariff and Olson, 1997;Nishikimi et al, 2001;Mitchell et al, 2004) and is also abundant in the somatic compartments of the ovary (Zackrisson et al, 1996;Jablonka-Shariff and Olson, 1997;Jablonka-Shariff et al, 1999;Nakamura et al, 1999;Yamagata et al, 2002;Mitchell et al, 2004). The expression and distribution of eNOS in porcine oocytes do not deviate from this pattern Takesue et al, 2003).…”
Section: Discussionsupporting
confidence: 83%
“…The expression of all three NOS proteins in one cell type is not surprising; it is known that the expression of several NOS isoforms occurs both in somatic cells (Mehta et al, 1995) and in mammalian oocytes (Zackrisson et al, 1996;Jablonka-Shariff and Olson, 1997;Tao et al, 1997;Jablonka-Shariff et al, 1999). The expression of NOS mRNA was also observed in the cumulus and granulosa cells which enclose the oocyte during its growth period.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the rat, Zhang et al (2011) demonstrated cellular expression and immunolocalization of three different NOS isoforms in the ovary before puberty. In adult rats, several authors assessed the expression of eNOS in granulosa cells, thecal layer, and ovarian stroma (Zackrisson et al 1996, Jablonka-Shariff & Olson 1997, Jablonka-Shariff et al 1999, Nakamura et al 1999, while iNOS was localized only in somatic cells of follicle and luteal cells (JablonkaShariff & Olson 1997, Tao et al 1997. Even though eNOS has been considered a constitutively expressed enzyme isoform, many experimental works document that the pattern of protein and mRNA expression within the ovary is subjected to changes during follicular and luteal phases of the estrous cycle.…”
Section: Regulation Of No Productionmentioning
confidence: 99%
“…This transition may be due to local transformation of mesenchymal cells into endothelial cells or active migration of endothelial cell precursors from preexisting blood vessels. Apart from the effect of NO on follicular blood flow demonstrated in the rat (Griffith 1994, Zackrisson et al 2000, Mitsube et al 2002 and human (Zackrisson et al 1996), suppressive effects of NO on angiogenesis in the bovine follicle have been postulated by observing a negative relationship between VEGF and NO levels in porcine granulosa cells (Grasselli et al 2002).…”
Section: Role Of No In the Control Of Follicular Angiogenesismentioning
confidence: 99%